Building Vocabulary Bridges: Exploring Pre-Service Primary School Teachers' Dispositions on L2 Vocabulary Instruction for Emergent Bilinguals through Interactive Book Reading - Eline Decraene; Silke Vanparys; Maribel Montero Perez; Hilde Van Keer (MDPI AG, 2023)
A strong vocabulary is crucial for language acquisition and can profoundly influence academic and societal success. Interactive book reading (IBR) offers an effective approach for vocabulary instruction as it provides a dynamic and engaging word-learning context. However, as children progress from preschool to primary grades, the emphasis on IBR declines, despite the persistent need for comprehensive literacy education, particularly for emergent bilinguals. This study aims to uncover the reasons underlying the diminishing use of IBR and focuses on the dispositions (i.e., knowledge and beliefs) of pre-service teachers regarding L2 vocabulary instruction during IBR with emergent bilinguals. Semi-structured interviews were conducted with 36 pre-service teachers in Flanders. Thematic analysis revealed a foundational knowledge base for vocabulary instruction during IBR, with most beliefs aligning with scientific evidence. Nevertheless, some beliefs contradicted research findings, particularly concerning the deliberate use of IBR to achieve specific learning objectives, harnessing students' home languages and fully realizing IBR's potential for optimal vocabulary acquisition. Furthermore, preconditions at the class, school, educational policy and parental levels emerged as crucial factors for effectively implementing vocabulary instruction during IBR. These findings serve as pivotal starting points for further refining pre-service teacher education and developing in-service professional development in Flanders.